Defining human-AI teaming the human-centered way: a scoping review and network analysis - Berretta, Sophie; Tausch, Alina; Ontrup, Greta; Gilles, Björn; Peifer, Corinna; Kluge, Annette (Frontiers in Artificial Intelligence, 2023)
With the advancement of technology and the increasing utilization of AI, the nature of human work is evolving, requiring individuals to collaborate not only with other humans but also with AI technologies to accomplish complex goals. This requires a shift in perspective from technologydriven questions to a human-centered research and design agenda putting people and evolving teams in the center of attention. A socio-technical approach is needed to view AI as more than just a technological tool, but as a team member, leading to the emergence of human-AI teaming (HAIT). In this new form of work, humans and AI synergistically combine their respective capabilities to accomplish shared goals. The aim of our work is to uncover current research streams on HAIT and derive a unified understanding of the construct through a bibliometric network analysis, a scoping review and synthetization of a definition from a socio-technical point of view. In addition, antecedents and outcomes examined in the literature are extracted to guide future research in this field. Through network analysis, five clusters with different research focuses on HAIT were identified. These clusters revolve around 1) human and 2) task-dependent variables, 3) AI explainability, 4) AI-driven robotic systems, and 5) the effects of AI performance on human perception. Despite these diverse research focuses, the current body of literature is predominantly driven by a technology-centric and engineering perspective, with no consistent definition or terminology of HAIT emerging to date. We propose a unifying definition combining a humancentered and team-oriented perspective as well as summarize what is still needed in future research regarding HAIT. Thus, this work contributes to support the idea of the Frontiers Research Topic of a theoretical and conceptual basis for humane work with AI systems.